2021
DOI: 10.3390/biomedicines9050531
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-Loaded Collagen/Hydroxyapatite Layers Electrospun on 3D Printed Titanium Implants Prevent Bone Destruction Associated with S. epidermidis Infection and Enhance Osseointegration

Abstract: The aim of the study was to develop an orthopedic implant coating in the form of vancomycin-loaded collagen/hydroxyapatite layers (COLHA+V) that combine the ability to prevent bone infection with the ability to promote enhanced osseointegration. The ability to prevent bone infection was investigated employing a rat model that simulated the clinically relevant implant-related introduction of bacterial contamination to the bone during a surgical procedure using a clinical isolate of Staphylococcus epidermidis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…In addition, Suchý et al constructed Van-loaded collagen/hydroxyapatite layers on the Ti-based implant via electrospun technology and 3D printing technology. They found that the composite coating could prevent the destruction of bone structure caused by bacterial infection and enhance osseointegration [ 79 ].…”
Section: Local Drug Delivery Systems With Ti-based Implantsmentioning
confidence: 99%
“…In addition, Suchý et al constructed Van-loaded collagen/hydroxyapatite layers on the Ti-based implant via electrospun technology and 3D printing technology. They found that the composite coating could prevent the destruction of bone structure caused by bacterial infection and enhance osseointegration [ 79 ].…”
Section: Local Drug Delivery Systems With Ti-based Implantsmentioning
confidence: 99%
“…Anti-adhesive agents in surface modifications (i.e., hydrophilic polymer brushes) provide coated surfaces that prevent initial bacterial adhesion; however, such architectures do not kill or inhibit biofilm growth, and the few adhered bacteria can over time still form a mature biofilm [181,182]. Therefore, to overcome this shortcoming and improve surface coatings, surface-anchored polymer brushes have been functionalized with antimicrobial agents to kill bacteria and inhibit biofilm development [32,[182][183][184][185].…”
Section: Surface Engineered Polymeric-brush-tethered Hdpsmentioning
confidence: 99%
“…Pharmaceutics 2021, 13, x FOR PEER REVIEW 14 of 24 surface coatings, surface-anchored polymer brushes have been functionalized with antimicrobial agents to kill bacteria and inhibit biofilm development [32,[182][183][184][185]. Among these antimicrobial agents, HDPs exhibit appealing features for designing antibiofilm surfaces (Figure 9).…”
Section: Surface Engineered Polymeric-brush-tethered Hdpsmentioning
confidence: 99%
“…In a rat model, Tomas et al [48] used S. epidermidis to contaminate orthopedic implants and simulate orthopedic implant infection, and added a vancomycin-loaded collagen/hydroxyapatite coating onto 3D-printed titanium (Ti) implants via electrospinning. Finally, the collagen/hydroxyapatite coating loaded with vancomycin was found to significantly kill S. epidermidis, prevent bone damage associated with S. epidermidis infection, and promote bone regeneration and integration.…”
Section: Vancomycinmentioning
confidence: 99%